2023
DOI: 10.7759/cureus.39789
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Luteolin Against Ehrlich Solid Carcinoma in Rats via Blocking Wnt/β-Catenin/SMAD4 Pathway

Heba Aljohani,
Ahmed E Khodier,
Mohammed M Al-Gayyar

Abstract: BackgroundEhrlich solid carcinoma (ESC) is characterized by rapid proliferation and a short survival time. Because Ehrlich ascites carcinoma (EAC) resembles human cancer cells, Ehrlich solid and ascetic forms are commonly used to determine the anticancer effects of various compounds. Luteolin is a flavonoid compound found in many dietary sources, including carrots, peppers, celery, olive oil, peppermint, and oregano. Luteolin has potent anti-inflammatory, antidiabetic, antitumor, and antiapoptotic activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In YQQYJDF, the core active ingredients corresponding to these five target genes are luteolin, quercetin, kaempferol and stigmasterol. Luteolin is a natural flavone compound that is considered to have antitumor effects [ 37 , 38 ]. Some studies have confirmed that luteolin can significantly inhibit glioma cell proliferation, migration, and invasion and induce their apoptosis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In YQQYJDF, the core active ingredients corresponding to these five target genes are luteolin, quercetin, kaempferol and stigmasterol. Luteolin is a natural flavone compound that is considered to have antitumor effects [ 37 , 38 ]. Some studies have confirmed that luteolin can significantly inhibit glioma cell proliferation, migration, and invasion and induce their apoptosis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rats were subjected to intramuscular injection of 0.15 ml Ehrlich cells (2×10 6 ) in the thigh of the left hind leg [9,10].…”
Section: Esc Groupmentioning
confidence: 99%
“…During the experiment period, the control group did not receive any treatment. In contrast, the ESC group was given an intramuscular injection of 0.15 mL 2×10 6 Ehrlich cells in the thigh of the left hind leg [7][8][9]. In the ESC group treated with arctiin, we induced ESC in rats.…”
Section: Animals' Treatmentmentioning
confidence: 99%